THE ROLE OF YOUTH IN CREATING A NEW ENLIGHTENED SOCIETY IN UZBEKISTAN (Conference Zone, 2022)
This article talks about the prosperity of our country and the contribution of young people to it. The concept of "New Uzbekistan - an enlightened society" and a national program for its implementation will be developed